Efficacy and Safety of Apixaban, Dabigatran, Rivaroxaban, and Warfarin in Asians With Nonvalvular Atrial Fibrillation. Issue 8 (11 September 0207) - Chan, Yi‐Hsin; See, Lai‐Chu; Tu, Hui‐Tzu; Yeh, Yung‐Hsin; Chang, Shang‐Hung; Wu, Lung‐Sheng; Lee, Hsin‐Fu; Wang, Chun‐Li; Kuo, Chang‐Fu; Kuo, Chi‐Tai
Abstract : Background: Whether non–vitamin K antagonist oral anticoagulants (NOACs) are superior to warfarin among Asians with nonvalvular atrial fibrillation remains unclear. Methods and Results: In this nationwide retrospective cohort study collected from Taiwan National Health Insurance Research Database, there were 5843, 20 079, 27 777, and 19 375 nonvalvular atrial fibrillation patients taking apixaban, dabigatran, rivaroxaban and warfarin, respectively, from June 1, 2012 to December 31, 2016. Propensity‐score weighting was used to balance covariates across study groups. Patients were followed until the first occurrence of any efficacy or safety outcome or the end date of study. Hazard ratios (95% confidence intervals) comparing apixaban, dabigatran, and rivaroxaban with warfarin were: ischemic stroke/systemic embolism (IS/SE), 0.55 (0.43–0.69), 0.82 (0.68–0.98), and 0.81 (0.67–0.97); major bleeding, 0.41 (0.31–0.53), 0.65 (0.53–0.80), and 0.58 (0.46–0.72); and all‐cause mortality, 0.58 (0.51–0.66), 0.61 (0.54–0.68), and 0.57 (0.51–0.65). A total of 3623 (62%), 17 760 (88%), and 26 000 (94%) patients were taking low‐dose apixaban (2.5 mg twice daily), dabigatran (110 mg twice daily), and rivaroxaban (10–15 mg once daily), respectively. Similar to all‐dose NOACs, all low‐dose NOACs had lower risk of IS/SE, major bleeding, and mortality when compared with warfarin. In contrast to other standard‐dose NOACs, apixaban was associated with lower risks of IS/SE (0.45 [0.31–0.65]), major bleeding (0.29 [0.18–0.46]), and mortality (0.23 [0.17–0.31]) than warfarin. Conclusions: All NOACs were associated with lower risk of IS/SE, major bleeding, and mortality compared with warfarin in the largest real‐world practice among Asians with nonvalvular atrial fibrillation. All low‐dose NOACs had lower risk of IS/SE, major bleeding, and mortality when compared with warfarin. Standard‐dose apixaban caused a lower risk of IS/SE, major bleeding, and mortality compared with warfarin.